(untitled) (The Pakistan Development Review, 2006)
This paper argues that a return to corporatist governance structures is impossible in Pakistan. Section 1 outlines neo-classical labour market regulation rationalities presented by Hayek, Wieser, and Sen. Section 2 compares and contrasts Fordist and Post-Fordist modes of labour market regulation. And Section 3 seeks to establish the impossibility of institutionalising corporatist governance structures in the labour markets of Pakistan. Neo-classical theory sees relations between labour and the representatives of capital (‘managers’) as relations created spontaneously by individuals in the pursuit of their rational self-interest. The capitalist individual, be he labourer or manager, defines ‘maximisation of utility’ as his ‘rational self interest’, and order within the labour market requires a reconciliation of individual (the labourer’s) and aggregate (the manager’s) utility maximisation (with aggregate utility maximisation being represented by shareholders value). Labour market order is thus impeded if: